2022
DOI: 10.1111/jth.15642
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin in complex with dabigatran can still interact with PAR‐1 via exosite‐I and instigate loss of vascular integrity

Abstract: Background: Atrial fibrillation (AF) can lead to the loss of microvascular integrity thereby enhancing AF progression. Mechanistically, the pro-coagulant state that drives the risk of stroke in patients with AF may also play a causal role in microvascular loss. Direct oral anticoagulants (DOACs), the preferred anticoagulants for AF, can target factors upstream (factor Xa [FXa]) or downstream (thrombin) in the coagulation cascade and mediate differential vascular effects through interaction with proteaseactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Therefore, a role for the coagulome in the microvascular rarefaction that drives the pro-fibrotic substrate for AF is under active investigation. For instance, a recent paper by Dolleman et al explored the impact of DOACs on vascular integrity in vitro using platelet-free plasma in thrombin generation-and endothelial barrier assays (57). Interestingly, they demonstrated that while the anti-FXa DOAC rivaroxaban and the anti-thrombin DOAC dabigatran are both efficient in blocking their target proteases, rivaroxaban could preserve endothelial barrier function while dabigatran failed to protect endothelial integrity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a role for the coagulome in the microvascular rarefaction that drives the pro-fibrotic substrate for AF is under active investigation. For instance, a recent paper by Dolleman et al explored the impact of DOACs on vascular integrity in vitro using platelet-free plasma in thrombin generation-and endothelial barrier assays (57). Interestingly, they demonstrated that while the anti-FXa DOAC rivaroxaban and the anti-thrombin DOAC dabigatran are both efficient in blocking their target proteases, rivaroxaban could preserve endothelial barrier function while dabigatran failed to protect endothelial integrity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For instance, a recent paper by Dólleman et al explored the impact of DOACs on vascular integrity in vitro using platelet-free plasma in thrombin generation and endothelial barrier assays. 63 Interestingly, they demonstrated that while the anti-FXa DOAC rivaroxaban and the antithrombin DOAC dabigatran are both efficient in blocking their target proteases, rivaroxaban could preserve endothelial barrier function while dabigatran failed to protect endothelial integrity. The barrier disrupting effect of dabigatran could be prevented in the presence of a custom-made peptide that blocks thrombin's exosite-I.…”
Section: Theme 1: the “Coagulome” As A Critical Driver Of Cardiovascu...mentioning
confidence: 99%